Hemogram responses in goats toward challenged with Corynebacterium pseudotuberculosis and its immunogen mycolic acids - Ahmed Odhah, Mohammed Naji; Abdullah, Faez Firdaus Jesse; Haron, Abd Wahid; Mohd. Lila, Mohd. Azmi; Saad, Mohd. Zamri; Khuder, Zaid; Hambali, Idris Umar; Umar, Muhammed; Mohammed Saleh, Wessam Monther (Veterinary World, 2017)
Aim: This study was conducted to analyze the changes in blood profile of goats inoculated with Corynebacterium pseudotuberculosis and its immunogen mycolic acid (MA) extract. Materials and Methods: A total of 12 clinically healthy crossbred Boer female goats were divided into three groups; A, B and C (4 goats each per group). Group A was inoculated with 2 ml sterile phosphate buffered saline via intradermal route as the negative control group whilst Group B was inoculated with 2 ml of MA extract (1 g/ml) intradermally and Group C was then inoculated with 2 ml (1×109) colony forming unit of active C. pseudotuberculosis intradermally. Blood sample was collected aseptically from the jugular vein periodically for complete blood count (CBC) analysis throughout the experimental period (3 months). Result: A significant decrease (p<0.05) was observed in red blood cells, hemoglobin (Hb), packed cell volume, mean corpuscular volume and mean corpuscular Hb concentration in Groups B and C as compared to the control while WBCs, neutrophil, lymphocyte and basophil showed a significant increase (p<0.05) as compared to the control. Conclusion: The inoculation of C. pseudotuberculosis and MA resulted in a significant change in the CBC, thereby, indicating that MA has a role in caseous lymphadenitis pathogenesis.